The Theme of Pride in Old English Poetry - Caie, Douglas Graham (My University, 1969)
The examination of the theme of pride in Old English poetry begins with a detailed linguistic analysis of the various words for pride, ofermod, oferygd and wlenco in particular. Once conclusions have been drawn as to the precise meanings of the words in their poetic context and this linguistic information used to elucidate certain passages in Old English poetry, there follows an investigation of the origins of the theme and the reasons why it should have so fascinated the early medieval poet. In the second half of the thesis is an analysis of the Junius Manuscript, beginning with a detailed textual analysis of Daniel, in an attempt to show that the poetry is largely thematic and didactic. The theme of the manuscript is largely a warning against pride, conveyed to the audience by the use of the highly associative stock epithets and imaginative patterns which give the poetry a structural unity, rather that the faithful rendering in verse of the individual biblical narratives.
Keywords: English Language and Literature; English Language and Literature